Penilaian Kinerja Penyelenggara Pelayanan Publik Berdasarkan Permenpan Nomor 29 Tahun 2022 pada Kecamatan Sukolilo Kota Surabaya - Aisyah, Farsya Audria (VISA: Journal of Vision and Ideas, 2024)
This research aimed to examine the public service performance based on the regulation of Minister of Administrative Reform (PermenPAN) number 29 in 2022 at Kecamatan Sukolilo through six aspects of measurement. While, the research was descriptive qualitative with a case study approach. Data collection techniques in the research are interview, observation and documentation. The research result concluded Kecamatan Sukolilo performance in public service had run well. It could be seen from the aspects of service policy with the availability of standard information and service notice as the operator’s obligation in serving, the availability of community aspirations to improve their performance; professionalism aspects i.e. the responsive and time efficiency service and also competent to the service types, readiness and service culture (it reflects service providers were ready to serve according to the employee code of ethics); the availability of facilities in providing a service which included for disable users; the aspect of information system of public service in order to inform and support the service operational which werw known by the public; the availability of a special consultation and complaint place in providing information and clarification; the existence of public service innovations in making online licensing service easier to be made.